The Use of Drone Technology for Project Monitoring in Construction Sites - Abdullah, Abdul Rahman; Seow, Ta Wee (Research in Management of Technology and Business, 2023)
Drones are not excluded from appearing in the construction sector in this current age of technology growth. Numerous areas such as mine mapping and transportation surveillance, are exhibiting increased interest in using drones. Malaysia’s construction industry continues to face numerous challenges, including low quality, low productivity, inexperienced labor, project delays, poor maintenance, non-conducive working conditions, and high accident rates. Even though the issues faced by the construction industry during the construction stage are constantly being researched, there are still insufficient studies that provide an overview of the topic regarding the use of drones in the Malaysia construction sector. This study objectives are to study the factors that hinder the use of drone technology for project monitoring in construction sites and to identify steps that can be taken to overcome the factor that hinder the use of drone for project monitoring in construction sites. This study involved quantitative method which is questionnaires to G7 construction companies in Melaka and only 64 sets of the surveys with 52.03% response rate returned. All data was analysed using SPSS descriptive statistics. The findings show that the main factor that hinder the use of drone technology for project monitoring in construction sites is drone operation control and main step that can be taken is battery replacement. This study will contribute to improving industry participants’ understanding of drone use in construction, which will lead to an increase in drone users in the industry.